PENGARUH BUDAYA ORGANISASI HIJAU, KEPEMIMPINAN LINGKUNGAN, MANAJEMEN RANTAI PASOKAN HIJAU DAN PEMASARAN HIJAU TERHADAP FINANCIAL PERFORMANCE - Dimas Yuanito Yudisira Putra; Khomsiyah Khomsiyah (STMIK Widuri Jakarta, 2023)
The purpose of this study is to ascertain the relationship between financial performance and green organisational culture, environmental leadership, green supply chain management, and green marketing. 108 Consumer Cyclical sector companies listed on the Indonesia Stock Exchange (IDX) made up the study's sample. Information gleaned from secondary sources, such as annual reports and sustainability reports. This study employed multiple linear regression analysis as its analysis method. The findings of this study are independently based on the research that has been done. Corporate Financial Performance (Net Profit Margin) is positively impacted by green organisational culture, green supply chain management, and green marketing; environmental leadership has no impact on this metric. The cash ratio of a company is positively impacted by green organisational culture, environmental leadership, and green marketing; however, green supply chain management has little impact on cash ratio.